Introspective (Emotional) and Rational (financial) Factors Influencing the Decision of Private Investors, Business Angels (BA), to Invest in Unlisted Companies - Sanjuan, Jordi Mercader; Pruñonosa, Josep Torres; Martínez, Raul Gómez (Journal of Cultural Analysis and Social Change, 2026)
This study analyses the emotional and introspective factors, as well as the financial and rational factors, that influence the investment decisions of Business Angels (BA) in unlisted companies. Based on a survey of 76 private investors, two composite indices—a financial approach and an emotional–introspective approach—are constructed, consistent with a dual theoretical operationalisation. Through descriptive, correlational and multivariate analyses, the results show that BAs’ investment decisions follow a hybrid architecture: emotional factors are associated with the intensity of risk exposure and investment patience, whilst financial factors shape return expectations and ex ante criteria. No pure investor typologies are identified, but rather gradients of decision-making emphasis, consistent with the literature on behavioural finance and informal venture capital.